2023
DOI: 10.1177/00469580231155716
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Glycemic Control and Factors Associated With Poor Glycemic Control: A Systematic Review and Meta-analysis

Abstract: The primary method for preventing health and health-related problems in diabetic people is glycemic control. Numerous studies have documented the importance of glycemic control and the factors that influence it. However, the results are dispersed. This study sought to identify the prevalence of poor glycemic control and associated factors in Ethiopia. Findings will be crucial to reduce the burden of poor glycemic control. Comprehensive search was performed from databases: PubMed, Global Health, CINAHL, IRIS, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 124 publications
1
13
0
Order By: Relevance
“…The analysis revealed a significant improvement in treatment outcomes among patients with OGC compared to those with PGC. This finding is consistent with those of previous studies highlighting the importance of glycemic control in reducing the risk of complications and improving treatment responses in individuals with DM [ 17 , 18 ]. The ability to achieve OGC may enhance the body's immune response, leading to better control of the TB infection and a more favorable treatment outcome [ 19 ].…”
Section: Discussionsupporting
confidence: 93%
“…The analysis revealed a significant improvement in treatment outcomes among patients with OGC compared to those with PGC. This finding is consistent with those of previous studies highlighting the importance of glycemic control in reducing the risk of complications and improving treatment responses in individuals with DM [ 17 , 18 ]. The ability to achieve OGC may enhance the body's immune response, leading to better control of the TB infection and a more favorable treatment outcome [ 19 ].…”
Section: Discussionsupporting
confidence: 93%
“…The studies done have reported inconsistent ndings. Some researchers reported an association between alcohol use and treatment outcomes for HIV, hypertension, and diabetes mellitus (12)(13)(14) while other researchers reported no association (15)(16)(17). Findings from this study will help to inform interventions targeted at improving treatment outcomes of chronic diseases (HIV, hypertension, and diabetes mellitus.…”
Section: Introductionmentioning
confidence: 80%
“…Then, all exposures with p-value (< 0.20) are added in the multivariate modi ed Poisson regression (24) to determine the association of alcohol use and each chronic disease treatment outcome adjusting for other factors. The nal model also includes exposure variables considered as apriori confounders including sex, age, tobacco use and wealth index (12)(13)(14). Interaction terms among alcohol use and exposure variables (age and sex) are checked for all the four models and all are not statistically signi cant.…”
Section: Covariatesmentioning
confidence: 99%
“…However, it can be also the result of variations in practices, medical care and limited resources. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%